Interaction with the recombination hot spot chi in vivo converts the RecBCD enzyme of Escherichia coli into a chi-independent recombinase by inactivation of the RecD subunit. - Köppen, A (1995)
The RecBCD enzyme of Escherichia coli promotes recombination preferentially at chi nucleotide sequences and has in vivo helicase and strong duplex DNA exonuclease (exoV) activities. The enzyme without the RecD subunit, as in a recD null mutant, promotes recombination efficiently but independently of chi and has no nucleolytic activity. Employing phage lambda red gam crosses, phage T4 2- survival measurements, and exoV assays, it is shown that E. coli cells in which RecBCD has extensive opportunity to interact with linear chi-containing DNA (produced by rolling circle replication of a plasmid with chi or by bleomycin-induced fragmentation of the cellular chromosome) acquire the phenotype of a recD mutant and maintain this for approximately 2 h. It is concluded that RecBCD is converted into RecBC during interaction with chi by irreversible inactivation of RecD. After conversion, the enzyme is released and initiates recombination on other DNA molecules in a chi-independent fashion. Overexpression of recD+ (from a plasmid) prevented the phenotypic change and providing RecD after the change restored chi-stimulated recombination. The observed recA+ dependence of the downregulation of exoV could explain the previously noted "reckless" DNA degradation of recA mutants. It is proposed that chi sites are regulatory elements for the RecBCD to RecBC switch and thereby function as cis- and trans-acting stimulators of RecBC-dependent recombination.